Russian commercial policies and the European Union: Can Russia be anchored in a legal international economic order? - Iana Dreyer; Brian Hindley (European Centre for International Political Economy (ECIPE), 2008)
This paper explores whether Russia can be made to abide by international commercial rules. It discusses the role the EU, Russia's main trading partner, can and should play in fostering better Russian compliance with international commercial rules. Russia's economic revival, built on oil and gas, has been accompanied by increasing assertiveness in foreign policies, in which arbitrary trade measures and unlawful treatment of foreign investors have played an important role. Russia being outside many international treaties that shape the rules of international commerce, such as the GATT/WTO, Russia's partners in Europe have seemed to have no recourse. The Energy Charter Treaty has not been used to bring Russia into the fold of market-based rules in the energy sector. The European Union's PCA with Russia has been ineffective. The fragmentation of the EU's market in energy weakens its position in negotiations with Russia. This paper argues that governments and businesses should better leverage the existing legal arrangements, such as the Energy Charter Treaty and the existing bilateral investment treaties: these have not been used to their full potential. For the EU, Russia's WTO accession should continue to be regarded as a pre-requisite for the negotiation for a Common Economic Space. But WTO accession will not solve the EU's problem of power asymmetry in the energy sector. During the coming negotiations, the EU should consider dropping its usual method of regulatory embrace. It should rather focus on core market access issues, strong dispute settlement and adoption of international standards for regulation in business and industry.
Keywords: 330